(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article explores the importance of games as an active methodology in the educational context, highlighting the benefits this approach offers for teaching and learning. Active methodology, which places students at the center of the educational process, aims to promote a more engaging and meaningful learning experience. Games, when incorporated as a pedagogical tool, provide an interactive and dynamic environment that stimulates students’ active participation. Games offer several advantages, including increased student motivation and engagement. Through challenges and rewards, games make learning more appealing and stimulating, facilitating a deeper understanding of concepts. Additionally, games promote the development of essential skills, such as problem-solving, collaboration, and communication. By working in teams and facing challenges, students enhance their social and emotional competencies. Active methodology also fosters personalized learning. Games allow for adjustments in challenges according to individual students’ needs, contributing to a more tailored and effective educational experience. Finally, games can improve formative assessment by providing continuous feedback and enabling adjustments to teaching strategies. In summary, using games as an active methodology represents an innovative approach that transforms teaching, making it more interactive, adaptive, and motivating.